2020
DOI: 10.1088/1674-1056/ab889b
|View full text |Cite
|
Sign up to set email alerts
|

Tunable deconfined quantum criticality and interplay of different valence-bond solid phases*

Abstract: We use quantum Monte Carlo simulations to study a quantum S = 1/2 spin model with competing multi-spin interactions. We find a quantum phase transition between a columnar valence-bond solid (cVBS) and a Néel antiferromagnet (AFM), as in the scenario of deconfined quantum-critical points, as well as a transition between the AFM and a staggered valence-bond solid (sVBS). By continuously varying a parameter, the sVBS-AFM and AFM-cVBS boundaries merge into a direct sVBS-cVBS transition. Unlike previous models with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 64 publications
(193 reference statements)
2
17
0
Order By: Relevance
“…In spin-isotropic systems such as the J-Q 2 and J-Q 3 models with a columnar arrangement of the singlet projectors, no clear-cut signs of firstorder transitions have been observed, though there are unusual scaling corrections [52,59] that have also been interpreted as a consequence of a weak first-order transition [23,50,57,73,74]. By introducing other types of Q interactions in a J-Q 3 model with columnar Q 3 interactions, it was recently found that the DQC point can evolve to a clearly first-order transition [126]. It is also interesting to study columnar J-Q n models with Q terms containing more than n = 3 singlet projectors.…”
Section: B First-order Transitions and Emergent Symmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…In spin-isotropic systems such as the J-Q 2 and J-Q 3 models with a columnar arrangement of the singlet projectors, no clear-cut signs of firstorder transitions have been observed, though there are unusual scaling corrections [52,59] that have also been interpreted as a consequence of a weak first-order transition [23,50,57,73,74]. By introducing other types of Q interactions in a J-Q 3 model with columnar Q 3 interactions, it was recently found that the DQC point can evolve to a clearly first-order transition [126]. It is also interesting to study columnar J-Q n models with Q terms containing more than n = 3 singlet projectors.…”
Section: B First-order Transitions and Emergent Symmetrymentioning
confidence: 99%
“…Another interesting prospect is to mix different kinds of Q terms and investigate the interplay between interactions favoring PVBS and CVBS states (in a way similar to what was recently done with competing interactions favoring CVBS and staggered VBS states [126]). It may be possible in this way to design a Hamiltonian which can be fine-tuned to have an eightfold degenerate VBS state, with both CVBS and PVBS order.…”
Section: Future Prospectsmentioning
confidence: 99%
“…In spin-isotropic systems such as the J-Q 2 and J-Q 3 models with a columnar arrangement of the singlet projectors, no clear-cut signs of firstorder transitions have been observed, though there are unusual scaling corrections [52,59] that have also been interpreted as a consequence of a weak first-order transition [23,50,57,73,74]. By introducing other types of Q interactions in a J-Q 3 model with columnar Q 3 interactions, it was recently found that the DQC point can evolve to a clearly first-order transition [122]. It is also interesting to study columnar J-Q n models with Q terms containing more than n = 3 singlet projectors.…”
Section: B First-order Transitions and Emergent Symmetrymentioning
confidence: 99%
“…Moreover, it has recently been argued that the DQCP is actually a multicritical point [63,64]; a second relevant scaling field with all the symmetries of the Hamiltonian was detected in the conventional critical J-Q model [63], for which motivation was found in a deformed self-dual field theory [64]. In the J-Q model it was found that the system flows toward a first-order transition when a certain interaction is turned on in such a way as to maintain a sign-free path integral [60]. It is possible that the interaction with the opposite sign could instead open up an SL phase.…”
mentioning
confidence: 96%
“…In some variants of the J-Q model, clearly first-order transitions were observed [5,60,61]. The "checker-board" J-Q (CBJQ) model [5] (and a closely related loop model [62]) has a Z 2 breaking PS phase like that in the SS model.…”
mentioning
confidence: 99%